1996
DOI: 10.1046/j.1365-2567.1996.d01-751.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of macrophage migration inhibitory factor in murine neonatal calvariae and osteoblasts

Abstract: SUMMARYBone resorption and formation are dynamic processes that occur in both normal and injured bone tissues. Regulation of these processes is mediated at the local level by cytokines and growth factors. Macrophage migration inhibitory factor (MIF) is one of the proinflammatory cytokines that activates macrophages and regulates production of other cytokines, such as tumour necrosis factor-a and interleukin-1. We here demonstrate, by reverse transcription-polymerase chain reaction, high expression of MIF mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…We found significant up-regulation of MMP-9 mRNA, and a slight increase of MMP-2 mRNA, consistent with a previous finding (43). Considering these facts, including our previous report revealing high expression of MIF in murine osteoblasts (17), it is likely that MIF may act on osteoblasts as an autocrine factor promoting bone resorption rather than bone formation. Indeed, MIF-overexpressing transgenic mouse (16-week-old) shows signs of osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found significant up-regulation of MMP-9 mRNA, and a slight increase of MMP-2 mRNA, consistent with a previous finding (43). Considering these facts, including our previous report revealing high expression of MIF in murine osteoblasts (17), it is likely that MIF may act on osteoblasts as an autocrine factor promoting bone resorption rather than bone formation. Indeed, MIF-overexpressing transgenic mouse (16-week-old) shows signs of osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, we demonstrated that mouse osteoblasts expressed high amounts of MIF (17); however, its pathophysiological role in the bone tissues remains to be elucidated. We herein report for the first time that MIF enhances the MMP-13 mRNA level in osteoblasts obtained from newborn rat calvariae.…”
mentioning
confidence: 94%
“…The involvement of MIF in cell differentiation and proliferation has been reported. MIF is present in highly proliferative tissues such as the corneal epithelium, basal cell layers of the skin epidermis, neonatal rat calvaria, and the early embryonal chicken lens (Wistow et al 1993;Matsuda et al 1996;Onodera et al 1996;Shimizu et al 1996). MIF also promotes proliferation of fibroblasts (Mitchell et al 1999;Lacey et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that MIF elevated the content of MMP-13 (collagenase 3) mRNA in rat osteoblasts [10]. High level of MIF mRNA expression in MC3T3-E1 mouse osteoblasts was noted [11].…”
mentioning
confidence: 95%